The Influence of Principal Leadership, Rewards from Principals, and Punishment from Principals on Teacher Discipline in State Elementary Schools in Dumai City District, Dumai City - Syuhada Syuhada; Mahdum Mahdum; Gimin Gimin (Journal of Educational Sciences, 2022)
This research is a quantitative research with the Expost Facto method which aims to analyze and describe the influence of Principal Leadership, Rewards from Principals, and Punishment from Principals on Teacher Discipline either partially or simultaneously. Data were collected using an instrument in the form of a closed questionnaire which was distributed to 93 respondents consisting of public elementary school teachers in the Dumai Kota Sub-district after being tested for validity and reliability first. The results of the study using multiple linear regression analysis techniques concluded that partially Principal Leadership has a significant and positive effect on Teacher Discipline by 24.25% and is the most dominant factor in influencing teacher discipline in this study, Reward from the Principal has a significant and positive effect on Teacher Discipline by 4.41%, Punishment from the Principal has a significant and positive effect on Teacher Discipline by 20.46%. Meanwhile, simultaneously the Principal's Leadership, Reward from Principal, and Punishment from Principal have a significant and positive effect on Teacher Discipline by 49.1%, while the remaining 50.9% is influenced by other variables outside of this study. This indicates that the principal’s leadership, reward and punishments from the principal do have an influence toward teacher discipline.